Impact of Antibiotic Misuse on Human Microbiome and Rise of Opportunistic Infections (Development Engineering Conferences Center Articles Database, 2025)
Excessive and inappropriate antibiotic use has emerged as a critical factor disrupting human microbiome homeostasis, leading to decreased microbial diversity, overgrowth of opportunistic pathogens, and long-term metabolic, immunological, and neuropsychiatric consequences. Reduced populations of beneficial bacteria such as Lactobacillus and Bifidobacterium compromise short-chain fatty acid production, mucosal barrier integrity, and immune modulation, while facilitating the proliferation of antibiotic-resistant and opportunistic species like Clostridioides difficile and Enterobacteriaceae. These changes elevate systemic inflammation, alter host metabolism, and impact mental health via the microbiome-gut-brain axis. Advanced diagnostic tools, including shotgun metagenomics, 16S rRNA sequencing, metatranscriptomics, resistome, and mobile genetic element analysis, provide precise insights into microbiome disruption, functional impairments, and resistance gene dynamics. To mitigate these effects, rational prescription strategies, antimicrobial stewardship programs, microbiome-targeted interventions such as probiotics and fecal microbiota transplantation (FMT), and public health initiatives including education and policy regulation are essential. Implementing these measures can restore microbial balance, limit the emergence of resistant pathogens, and protect both physical and mental health, highlighting the need for integrated approaches to antibiotic use management.